ANTESEDEN CUSTOMER LOYALTY - Lestari, Desi; Ganawati (Transpublika Publisher, 2023)
The aim of this study is to determine the influence factors of e-commerce Service Quality Logistics on Customer Satisfaction and Customer Loyalty. The population in this study are Shopee e-commerce users in Bekasi. The sampling technique used was purposive sampling with 198 respondents. This type of research is quantitative research with data collection techniques distributing questionnaires via Google form using a Likert scale of 1 to 5. This research uses the Structural Equation Modeling (SEM) method through the AMOS software program to process data. The results showed that Order Accuracy had no positive effect on Customer Satisfaction, Order Condition had no positive effect on Customer Satisfaction, Timeliness had no positive effect on Customer Satisfaction, Order Discrepancy Handling had a positive effect on Customer Satisfaction, Customer Satisfaction had a positive effect on Customer Loyalty.